Contribution of Inheritance Assets by Islamic Law for Inheritance Recipients as Community Education - Muchtarom (The International Journal of Law Review and State Administration, 2024)
This research aims to find out the distribution of inheritance which is divided equally between men and women, and the practice of dividing inheritance regarding contributions to heirs. This research method is a qualitative approach, which describes the research object that occurs in the field. The data collection techniques used were interviews, observation, and documentation. Data analysis was carried out including data reduction, data presentation, and verification withdrawal. The results of the research reveal that: (1) Heirs receive assets equally between men and women through family consultation. After the assets are divided, there are remaining assets that are allocated by the heir to an heir who contributes to the heir during his or her lifetime. (2) The heirs who contribute to the inheritance receive more inheritance than the remaining assets after dividing them equally. The remaining assets in Islamic Inheritance, especially from a legal perspective, are not justified. Because, in Maqaşid shari'ah al-Khamsah, protection of religion is not implemented in society in terms of the division of inheritance between men and women. However, protection for the existence of religious descendants, as well as protection for assets, all of which are at a secondary or tertiary level, have been fulfilled.